2009
DOI: 10.2141/jpsa.46.112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Mulberry Leaves (Morus alba L.) on Egg Yolk Color

Abstract: To investigate the e ects of dietary mulberry leaves on egg yolk color and egg quality, a total of laying hen CP Brown were randomly allotted into groups with replicate of chickens per replicates. Each replicate was furthermore divided into large cages ( cm) with birds. Dried mulberry leaves were supplemented to a basal diet ( . CP, kcal/kg ME) at (control), , and for days. Compared to control, any adverse e ects were not observed in feed intake, body weight gain, egg production rate, egg weight, yolk weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 8 publications
1
15
1
2
Order By: Relevance
“…The primary sources of xanthophylls are corn, corn gluten meal, and dehydrated alfalfa meal [5]. Concentrated pigments can also be induced from natural sources, such as fall leaves (mulberry) [6,7], flowers (narcissus, marigold), fruits (pineapple, citrus fruits, paprika) [8], vegetables (carrots, tomatoes), insects (ladybugs), bird plumage (flamingo, cock-of-the-rock, ibis, canary), marine animals (crustaceans, salmon) [9], and yeast (Phaffia rhodozyma) [10]. These pigments provide different colors, from light yellow to dark red [11].…”
Section: Description Of Problemmentioning
confidence: 99%
“…The primary sources of xanthophylls are corn, corn gluten meal, and dehydrated alfalfa meal [5]. Concentrated pigments can also be induced from natural sources, such as fall leaves (mulberry) [6,7], flowers (narcissus, marigold), fruits (pineapple, citrus fruits, paprika) [8], vegetables (carrots, tomatoes), insects (ladybugs), bird plumage (flamingo, cock-of-the-rock, ibis, canary), marine animals (crustaceans, salmon) [9], and yeast (Phaffia rhodozyma) [10]. These pigments provide different colors, from light yellow to dark red [11].…”
Section: Description Of Problemmentioning
confidence: 99%
“…Udedibie andOpara (1998), Odunsi (2003) and Akande et al (2007) also reported a reduction of feed intake with increased level of mulberry leaf meal in the diets of broilers and laying hens. In contrast, Kamruzzaman et al (2012) and Lokaewmanee et al (2009) had reported no adverse effect in feed intake up to 9 % inclusion of mulberry leaf meal in the ration. From weight gain perspective, Chowdary et al (2009) has reported that highest body weight gain was observed in 10% mulberry leaf meal inclusion.…”
Section: Resultsmentioning
confidence: 89%
“…In general, various blood components including mineral (Paik et al 2009), hormone (Yoshimura et al 2009) and lipophilic dye such as carotenoids (Lokaewmanee et al 2009) are transferred into the egg yolks by passing through the ovarian follicular layers. The yolk precursors released from blood capillaries also pass through gaps between granulosa cells and reach the oocyte plasma membrane, where the components are endocytosed into the oocyte cytoplasm.…”
Section: Discussionmentioning
confidence: 99%